OTENTISITAS HADITS MENURUT ABDULLAH AL-ASYI DALAM KITAB SYIFA' AL-QULUB - Wahid, Abd (ALQALAM, 2013)
This study tried to find an answer about the position of Sheikh Abdullah al - Asyi in terms of the authenticity of the Hadith. Can be formulated in more detail in the following questions: How does the quality of the hadith contained in the book Shifa' al-Qulub of Sheikh Abdullah al-Asyi?; How methods hadith mention in the book of Shifa' al -Qulub ; How is discussion authority of hadith in the Shifa' al-Qulub? According to the study authors, it can be concluded that: With regard to the quality of the hadith contained in this work, as far as the research that has been done, it can be said that there are several categories of hadith, there is a shahih, hasan and dha'if. The hadiths mention methods contained in the book Shifa' al-Qulub, in terms of the language used is the language Malay. While the script used is Arabic Jawi (jawi writing). In the hadith mention also, the author of this book does not mention the hadith texts in Arabic, both sanad and matan. In addition, the author also does not mention the source of the hadith collection of original sources. Based on the author's own admission, he does not mention the Arabic text, not to mention sanad and matan, and just take the intent or understanding of tradition alone. This, according to the author is to facilitate the readers, not boring and not spend a long time. Can also be explained, following the usual standards of scientific work today, it can be concluded that the reference to the Hadith without mentioning the sanad and matan, and sources, according to researchers in terms of scientific standards to be used as a less credible source or scientific references in scientific papers in present. Key words: Abdullah al-Asyi, Hadith, Authenticity